Fabrication and Dissolution of Americium Plutonium Oxide Fuels - de Visser – Týnová Eva; Bruin Jessica; Oud Frank (EPJ Web of Conferences)
As a part of the research on Gen IV oxide fuels the effect of the minor actinides (americium) on the dissolution behaviour of plutonium oxide has been studied. Two compositions of americium plutonium oxide pellets have been fabricated by powder metallurgy in a glovebox specially designed for work with americium. These fresh pellets have been dissolved in hot nitric acid and hot nitric acid with hydrofluoric acid. After a dissolution of 300 minutes, very limited dissolution of just few percent of the starting material was determined, where the dissolution rate of plutonium oxide is about 100 times lower comparing to americium oxide.